Agentes imunomoduladores na avaliação geriátrica ampla - França, Danielle Cristina Honorio (2022)
The Comprehensive Geriatric Assessment (CGA) is a way to analyze the health and quality of life of the elderly. Basic and instrumental daily activities may be compromised due to changes caused by infectious processes. Studies suggest possible immunological changes in infections, especially in respiratory viral infections in patients over 60 years of age. Thus, the aim of this study was to analyze the il-6, IL-10 and IL-17A cytokines and the hormone melatonin as immunomodulatory determinants in the Comprehensive Geriatric Assessment in patients with viral respiratory infection. The sample had the participation of 68 participants in different age groups, with positive and negative diagnosis for COVID-19. Blood samples were collected for cytokine quantification by the flow cytometry method and the hormone melatonin by ELISA method. In addition, structured and validated questionnaires were applied to evaluate basic (Katz) and instrumental (Lawton and Brody) activities. With this study, it was possible to arrive at the result that there is a directly proportional correlation between the concentration of IL-17 cytokine in elderly patients, with the degree of dependence, especially in relation to daily instrumental activities. In addition, there was an increase in IL-6 and melatonin in the infected group, and this increase was more evident in individuals under 60 years of age. The data from the present study allow us to conclude that melatonin and cytokines have an immunomodulatory role in SarsCoV-2 infection and that these parameters are different compared to the young groups with and without infection and elderly with and without infection. The considerable impact on the ability to perform instrumental activities of daily living of the elderly is an extremely important result, thus it is concluded that this data corroborates the greater need for attention on the part of public policies, which should aim at greater measures of prevention, promotion, treatment and monitoring of this population.